The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.36953/ecj.2019.20318
|View full text |Cite
|
Sign up to set email alerts
|

Distellery spent wash (DSW) treatment methodogies and challenges with special reference to incineration: An overview

Abstract: Biofuels are derived from renewable bio-mass resources and, therefore, provide a strategic advantage to promote sustainable development and to supplement conventional energy sources in meeting the rapidly increasing requirements for transportation fuels associated with high economic growth, as well as in meeting the energy needs of India's vast rural population. India is major producer of potable and industrial alcohols. The majority of distilleries use molasses as a feed stock. Ethyl alcohol is an important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In this process the wastewater is treated in a single tank using acidification, methane fermentation and sludge thickening processes without any heat and mixing (Bhardwaj et al, 2019).…”
Section: Conventional Digestermentioning
confidence: 99%
“…In this process the wastewater is treated in a single tank using acidification, methane fermentation and sludge thickening processes without any heat and mixing (Bhardwaj et al, 2019).…”
Section: Conventional Digestermentioning
confidence: 99%
“…It is guesstimated that about one third of this or 100 million tons of residues are not being utilized and are disposed of by burning them in the open fields (NPCMR, 2014). Unsustainable management practices of biomass waste would create high adverse environmental impacts (Ross, 2018;ruhela et al, 2020;Bhardwaj et al, 2019). Energy can be harvested from a biomass, a significant renewable energy source forever.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of spent wash on crop production is well recorded (Rajagopal et al, 2014;Pugazh et al, 2016) reported that total chlorophyll content, crop growth rate (CGR), total dry matter, and nutrient uptake all rose when distillery effluent was added (N, P and K). It was discovered that a one-time controlled application of diluted spentwash improved soil fertility and agricultural yields (Chandraju et al, 2013;Chopra et al, 2013;Bhardwaj et al, 2019;Ruhela et al, 2020). The availability of nutrients in distillery effluents, as well as the prospect of substituting them for inorganic fertiliser in agriculture, holds a lot of promise (Joshi and Singh, 2010).…”
Section: Introductionmentioning
confidence: 99%